Book Review: Copyright and E-learning: A Guide for Practitioners. Jane Secker, with Chris Morrison. - McCleskey, Sarah (Journal of Copyright in Education & Librarianship, 2018)
This review discusses the book Copyright and E-learning: A Guide for Practitioners by Jane Secker with Chris Morrison.